Monuments and historic buildings in the Netherlands and their historical geography (Bulletin KNOB, 2006)
The series ‘Monumenten in Nederland’ presents a splendid survey of the monumental buildings in the Netherlands. In the study - though not in the field yet - the series has taken the place of the time-honoured ‘Kunstreisboek’ (art guidebook). Compared to previous editions the latest edition of the ‘Kunstreisboek’ already paid more attention to the structure of villages and towns and thus to the context of the historic buildings. However, on this point there is still something to be desired. This contribution looks at the new series of books from a historical-geographical perspective and, more in general, at historic buildings and policy in connection with them in the Netherlands.In three ways a more geographical approach to the preservation of monuments and historic buildings would lead to changes in research and policy. In the first place, interest would shift from the most prominent historic buildings to the more representative bulk. Secondly, a geographical line of approach may offer new insights into the regional diversity of developments in building. Thirdly, geographical models for the development of historical towns and rural landscapes could be a means to predict historical values yet to be discovered.